Pengaruh Moral Pajak, Pengetahuan Perpajakan, dan Sosialisasi Perpajakan Pada Kepatuhan Wajib Pajak UMKM Badan - Nova Dewi, I Luh; Supadmi, Ni Luh (Innovative: Journal Of Social Science Research, 2024)
One effort to make the country independent in terms of national development funding is by exporting its source of costs, namely taxes. Community compliance in paying taxes has an important role in helping the government accelerate national development and finance regional spending which is increasing day by day. This study focuses on analyzing the impact of tax morale, tax knowledge, and tax socialization on corporate MSME taxpayer compliance. The location of this study is at KPP Pratama North Badung, the total sample used is 100 taxpayers who were calculated using the Slovin formula with the accidental sampling method. Data collection was carried out by distributing questionnaires. The analysis technique used is multiple linear regression analysis. The findings of this study reveal that tax morale, tax knowledge, and tax socialization have a positive influence on corporate MSME taxpayer compliance. The theoretical implication of this study is that it is able to explain the impact of tax morale, tax knowledge, and tax socialization on corporate MSME taxpayer compliance which is linked to attribution theory and compliance theory. The practical implication of this study is that it provides information and can be used as assessment material for the government and DJP to create tax policies in an effort to increase taxpayer compliance and for the North Badung Pratama KPP it is hoped that it will further increase tax socialization to deepen taxpayer knowledge, so that taxpayers will implement his obligations well.